Evolution Model for the Absheron Mud Volcano: From Stratified Sediments to Fluid Mud Generation. Issue 12 (4th December 2020) - Blouin, Arthur; Sultan, Nabil; Pierron, Alexandra; Imbert, Patrice; Callot, Jean‐Paul
Abstract: Submarine mud volcanoes (MVs) are one of the most spectacular methane expulsion features at the seafloor and they represent a significant geohazard worldwide. In this work, we focus on the physical processes controlling the initiation and early evolution of the Absheron mud volcano (AMV). Our analyses were carried out based on basin modeling calibrated thanks to existing seismic interpretation of the AMV, analysis of sediment samples from seabed, and data from two exploration wells. Acquired laboratory geotechnical data allowed us to derive laws considering the impact of gas exsolution on host sediment behaviors. In this study, we identified key geological and physical conditions that led to MV formation: by coupling diffusion processes with hydrofracturing and fluid advection, we were able to simulate the conditions required to generate mud 3.5 km below the AMV. Mud remobilization up to the seabed was reproduced by using Navier‐Stokes equations modified to account for the impact of gas expansion on mud density. Considering density inversion only, simulations indicate that mud would be extruded at the seabed 100 years after its generation, an ascent rate similar to extrusion rates measured at the active Kotyrdag MV in Azerbaijan. Plain Language Summary: Mud volcanoes (MVs) build‐up at the Earth surface from liquidized sediments remobilized from depths reaching several kilometers. They are distributed globally, onshore and offshore, in different geological backgrounds and represent serious geohazards for people and infrastructures. Moreover, they are also among the most spectacular methane expulsion features at the surface, participating to the global budget of green‐house gases emissions. Their understanding is thus paramount to prevent natural catastrophes such as Lusi eruption in Indonesia in 2006 and to quantify the human impact on global warming. If MVs are known for centuries (Pline the Elder) and studied for decades, little is known about the processes controlling mud generation from stiff deep sediments and its vertical migration toward the surface. The methane is often considered as being a driving element in this geological process and bubble formation in compacted sediments during laboratory testing led to strong damage of sediment properties. Here we develop two independent numerical models, based on simple physical processes and relying on in situ observations of the Absheron mud volcano (AMV, South Caspian Basin) and laboratory testing. They allow to simulate mud generation at depth and its remobilization to the surface. Our research work provides reliable information to describe the initiation and early evolution of an active MV. Key Points: Simulation of mud generation is possible through 2D basin modeling including the effect of gas Mud ascent through gas‐expansion‐driven density inversion is possible A semi‐quantitative formation model for the AMV is derived from modeling results